Water purification using a BiVO4/graphene oxide multifunctional hydrogel based on interfacial adsorption-enrichment and photocatalytic antibacterial activity. Issue 6 (15th March 2023) - Wang, Ruolin; Wu, Zhiting; Chen, Xiying; Cheng, Baijie; Ou, Wenhua
Abstract: Photocatalytic degradation by visible light-driven generation of reactive oxygen species shows great promise for purification of environmental water. However, such degradation is limited by the low separation efficiency of photogenerated carriers and the poor adsorption capacity of the photocatalyst itself. To solve these problems, we successfully constructed and prepared a composite hydrogel (BV-GH) combining a three-dimensional network structure composed of graphene oxide and BiVO4 to achieve the synergistic effects of adsorption enrichment and photocatalytic degradation. The results show that the amount of methylene blue and methyl orange adsorbed by BV-GH is 258.78 mg g −1 and 217.16 mg g −1, respectively, which is much higher than that obtained for pure BiVO4 . Due to the synergistic effect of adsorption enrichment and photocatalytic degradation, the degradation rate of the dye by BV-GH reaches 94.18% in 60 min, which is 6.98 times higher than that obtained for pure BiVO4 . Electron spin-resonance (ESR) experiments confirm that the main factor affecting the dye degradation by BV-GH is the ability to produce more ·OH and ·O2 −, which is an important reason for the excellent antibacterial performance of BV-GH against E. coli . This work can provide further inspiration for photocatalytic technology in water purification. Highlights: BiVO4 /GO hydrogel exhibits high adsorption properties for both anionic (MO) and cationic dyes (MB). The BV-GH2 hydrogel have better degradation efficiency for organic dyes than pure BiVO4 (∼6.98 times). The production of more reactive oxygen species allows the composite hydrogel to have even better antibacterial properties. BiVO4 /GO hydrogel shows high photocatalytic activities combined with adsorption-enrichment.